Mikroanalisis Kandungan Senyawa Fenolik Total Ekstrak Biji Kedelai dengan Reagen Folin-Ciocalteu - Yusnawan, Eriyanto; Utomo, Joko S (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2017)
One of the roles of phenolic compounds is as chemical defense system to inhibit the growth ofpathogen infection.Folin-Ciocalteu (FC) reagent is used to estimate total phenolic compounds spectrophotometrically. Microanalysis of the phenolic compounds using FC reagent is still limited.This study, therefore, aimed to develop a rapid method to estimate total phenolic compounds insoybean seed extract in a 96-well microplate. Optimum kinetic reaction was achieved after 90minutes of incubation. Response of 25 â€“ 1.000 Âµg ml-1 of gallic acid was linear (r = 0.99). Hundredsof samples could be analysed using the microplate 2 format in limited time, such as when workingwith soybean germplasm collection.